X-2Y+Z=7

-2X-Y-Z=-7

4X+5Y-2Z=3

There are many ways:

1. We get rid of Z by adding equation #1 and equation #2:

x-2y+z -2x-y-z = 7-7

-x -3y = 0

x = -3y

Now we can substitute x in the first equation

-3y-2y+z = 7

-5y +z = 7

z = 5y+7

now we can substitute x and z in the 3rd equation:

4* (-3y)+5y -2(5y+7) = 3 we get the value of y from this equation

-12y +5y -10y -14 =3

-17y = 17

y = -1

Now we can find values of x and z by putting value of y into:

x = -3 *(-1) = 3

z = 5 *(-1) + 7 = 2

Answer: X =3

Y = -1

Z = 2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up